Experimental study of 3-ply laminated glass beams subject to in-plane loads. (October 2021) - Riddell-Smith, Lauren; Cunningham, Lee; Mandal, Parthasarathi
Abstract: In this study, nineteen 3-ply laminated glass beams of 1.0 m span with different glass and interlayer types were tested to failure. Annealed glass beams generally failed in shear facture, whereas beams of toughened glass displayed lateral-torsional buckling (LTB) response, with a bow-shaped out-of-plane deflected shape and significant out-of-plane bending. The experimental failure loads had significant scatter for nominally similar beams, highlighting the variability of glass as a material. The loads have been compared to design predictions for LTB from published design methods, and it was found that many of the existing methods consistently over-estimate the LTB capacity of the beams, in some cases by more than three times the experimentally determined failure load.